Sex‐related variation in the vulnerability of wandering albatrosses to pelagic longline fleets. (24th November 2015) - Jiménez, S.; Domingo, A.; Brazeiro, A.; Defeo, O.; Wood, A. G.; Froy, H.; Xavier, J. C.; Phillips, R. A.
Abstract: The population of wandering albatrosses D iomedea exulans at South Georgia is decreasing because of bycatch in longline fisheries. Until at least the early 1990s, the survival rate of females was lower than males, consistent with the adult female‐biased bycatch reported for fisheries operating around the Brazil‐Falklands Confluence (BFC). Here we use extensive tracking data (1990–2012) from breeding birds at South Georgia to investigate overlap with longline fishing effort reported to the International Commission for the Conservation of Atlantic Tunas (ICCAT). Using data from multiple years, we conclude that breeding females are at higher risk than males from all the main pelagic longline fleets in the south‐west Atlantic. Our overlap index (based on fishing effort and bird distributions) correlated positively with numbers of ringed birds reported dead on longliners, indicating that the metric was a good proxy of bycatch risk. The consistent sex bias in overlap across years, and the likely resulting sex‐biased mortality, could account for lower adult female survival rate at the colony. The risk from fisheries changed seasonally; both sexes overlapped with pelagic longline effort during incubation (January–March), and particularly during post‐brood chick‐rearing (May–December), whereas overlap was negligible during brooding (April). The highest percentage of overlap was with the Taiwanese fleet, then vessels flagged to Brazil, Uruguay, Spain, Japan and Portugal. Females were consistently at greatest risk in the BFC region, whereas males showed lower and more variable levels of overlap with fisheries from 35 to 45°S. Our results have important implications for management of ICCAT longline fisheries and conservation of this highly threatened albatross population.